2019
DOI: 10.5797/jnet.tn.2018-0124
|View full text |Cite
|
Sign up to set email alerts
|

Left Distal Radial Approach for Stent-assisted Coiling of Left Vertebral Artery Aneurysm

Abstract: Objective:We report a first case of stent-assisted coiling for the left vertebral artery aneurysm via the left distal radial approach.Case Presentation: The patient was a 47-year-old male with unruptured left vertebral artery aneurysm. Transfemoral approach was infeasible because of the history of thoracoabdominal aortic dissection, the left distal radial approach was selected. Distal radial artery in the left anatomical snuffbox was punctured and a 4 Fr guiding sheath was introduced to the left vertebral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Simultaneous catheterization of the bilateral vertebral arteries was necessary; however, we decided to treat this case with bilateral dTRA because we had experience with left vertebral artery access via the left distal radial artery. 12,13) The modified Allen's test was negative (normal) for both hands, and ultrasound examination showed that the inner diameter of the radial artery at the snuffbox was 2.5 mm on the right side and 2.3 mm on the left side. These values are sufficiently larger than that of the outer diameter of the 4F sheath.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…Simultaneous catheterization of the bilateral vertebral arteries was necessary; however, we decided to treat this case with bilateral dTRA because we had experience with left vertebral artery access via the left distal radial artery. 12,13) The modified Allen's test was negative (normal) for both hands, and ultrasound examination showed that the inner diameter of the radial artery at the snuffbox was 2.5 mm on the right side and 2.3 mm on the left side. These values are sufficiently larger than that of the outer diameter of the 4F sheath.…”
Section: Case Reportmentioning
confidence: 99%
“…6) The conventional left-hand approach requires the operator to perform the procedure in an unfamiliar and uncomfortable posture, such as standing on the left side of the patient to perform the puncture, or striding over the patient's body from the right side of the patient to manipulate the catheter. However, we had previously reported the usefulness of left dTRA for left vertebral artery aneurysms, 12) and the patient's left hand was placed naturally on the abdomen in the left dTRA. This is close to the familiar puncture position in TFA and enables the operator to stand on the right side of the patient and perform the procedure in an ergonomically better posture similarly to TFA.…”
Section: Fig 4 Pre-(a) and Post-embolization (B) Of The Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation